2017
DOI: 10.1093/police/pax067
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Risks: Practitioner’s Perceptions of the Lottery of Mental Healthcare Available for Detainees in Custody

Abstract: The range and growing number of healthcare requirements being presented within custody environments has been widely debated (Rekrut-Lapa, T. and Lapa, A. (2014). ‘Health Needs of Detainees in Police Custody in England and Wales: Literature Review’. Journal of Forensic and Legal Medicine 69–75). Despite a number of reforms following the recommendations of the Bradley Review (Bradley (2009). Lord Bradley’s Review of People with Mental Health Problems or Learning Disabilities in the Criminal Justice System. Depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Hence it is likely staff are required to managed complex healthcare risks of detainees. (see Rekrut-Lapa and Lapa 2014;Skinns 2011;Williams et al 2017) As this chapter will demonstrate, the custody cell is a site where many of these risks, such as those of self-harm and violence, can be amplified. The cell, then, is a site of increased risk of harm where the 'corrosive effects of the custody environment' (Cummins 2008:41) can be observable.…”
Section: The Cell As a Site Of Physical And Emotional Riskmentioning
confidence: 96%
See 2 more Smart Citations
“…Hence it is likely staff are required to managed complex healthcare risks of detainees. (see Rekrut-Lapa and Lapa 2014;Skinns 2011;Williams et al 2017) As this chapter will demonstrate, the custody cell is a site where many of these risks, such as those of self-harm and violence, can be amplified. The cell, then, is a site of increased risk of harm where the 'corrosive effects of the custody environment' (Cummins 2008:41) can be observable.…”
Section: The Cell As a Site Of Physical And Emotional Riskmentioning
confidence: 96%
“…Frequently the cell is used to de-escalate situations, where detainees who are arrested and are too violent, uncooperative or incoherent through drink or drugs to be dealt with immediately, are taken straight to the cell. This makes the time a detainee is in a police cell an inherently risky period, where risk of suicide and self-harm is heightened (Williams et al 2017). As a result, the cell can be a place where the detainee exercises their power in the context of custody, resisting, being violent and, importantly, a place where emotions are actively managed by staff.…”
Section: Commented [Aw2r1]: Thanks!mentioning
confidence: 99%
See 1 more Smart Citation
“…The very complex relationship between decision-making and vulnerability is discussed later on but ensuring vulnerability is assessed correctly is essential for an effective investigation. Training for police officers involved in identifying vulnerability and mental health issues is poor and therefore officers can refer to their experiential knowledge to make decisions about categories of vulnerability (Williams et al, 2017). Having access to information, advice from and working with relevant expert partners, such as other health agencies and psychologists would be hugely beneficial.…”
Section: So Where Is the Evidence For This?mentioning
confidence: 99%
“…It should be stressed that this study does not examine the effectiveness of the risk assessment to identify all risks or vulnerabilities, clinical or otherwise. Recent studies investigating this issue have found that generally, the current risk assessments fail to identify a significant proportion of risks (Carter and Mayhew 2010, McKinnon and Grubin 2013, Noga et al 2015, Williams et al 2017 or identify vulnerable adults (Dehaghani 2016a(Dehaghani , 2016b.…”
Section: Introductionmentioning
confidence: 99%